Design of Novel Human Wrist Prostheses Based on Parallel Architectures: Dimensional Synthesis and Kinetostatics - Raffaele Di Gregorio (Biomimetics)
The human wrist affects the ability to efficiently perform many manipulation tasks. Despite this, most upper-limb prostheses are focused on the hand’s mobility, which makes users compensate for the lost wrist mobility with complex manipulation strategies relying on the mobility of other body parts. In this context, research on wrist prostheses is still open to new contributions, even though a number of such prostheses are already present in the literature and on the market. In particular, the potential uses of parallel mechanisms in wrist prosthesis design have not been fully explored yet. In this work, after recalling the mobility characteristics of human wrists and reviewing the literature both on wrist prostheses and parallel mechanisms, a number of parallel architectures employable in a wrist prosthesis are selected. Then, with reference to the design requirements of this prosthesis type, the dimensional synthesis and kinetostatic analysis of the selected architectures are addressed. The results of this work are new wrist prosthesis architectures together with the analysis of their kinetostatic performances. These findings complete the first step of a research project aimed at developing new concepts for mechatronic wrists.